2015
DOI: 10.1089/scd.2014.0273
|View full text |Cite
|
Sign up to set email alerts
|

A Decline in Wnt3a Signaling is Necessary for Mesenchymal Stem Cells to Proceed to Replicative Senescence

Abstract: Umbilical cord blood-derived mesenchymal stem cells are a promising source of cells for regeneration therapy due to their multipotency, high proliferative capacity, relatively noninvasive collection, and ready availability. However, extended cell culture inevitably triggers cellular senescence-the irreversible arrest of cell divisionthereby limiting the proliferative lifespan of adult stem cells. Wnt/b-catenin signaling plays a functional role as a key regulator of self-renewal and differentiation in mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…More importantly, Wnt signaling effector β-catenin showed a similar expression pattern to p27 suggesting a possible interaction between these two factors. A previous study also supports that Wnt signaling might be a predominant factor that could be used to overcome extensive passaging-induced cell aging in longterm cultured MSCs by directly intervening in the proliferative capacity and MSC senescence (Jeoung et al, 2015). In this study, we further discovered the underlying mechanism by using a unique cell sheet culture-induced cell aging system.…”
Section: Discussionsupporting
confidence: 60%
“…More importantly, Wnt signaling effector β-catenin showed a similar expression pattern to p27 suggesting a possible interaction between these two factors. A previous study also supports that Wnt signaling might be a predominant factor that could be used to overcome extensive passaging-induced cell aging in longterm cultured MSCs by directly intervening in the proliferative capacity and MSC senescence (Jeoung et al, 2015). In this study, we further discovered the underlying mechanism by using a unique cell sheet culture-induced cell aging system.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, we evaluated the presence of α-MSH and SCF, two important factors in the regulation of melanocyte differentiation and survival [ 43 , 44 ]. We also demonstrated that two modulators of the Wnt/β-catenin pathway, Wnt3a and Wnt10b, implicated in replicative senescence regulation [ 45 ] and in wound healing processes [ 46 , 47 ], respectively, are abundantly present in lipoaspirates. Overall, our data demonstrated a specific signature of adipose tissue secretome that does not overlap with circulating factors.…”
Section: Resultsmentioning
confidence: 99%
“…A histochemical staining kit (Sigma-Aldrich) was used according to the manufacturer's instructions to qualitatively assess SA b-gal activity, and cells were examined on an inverted microscope. To assess senescent-cell formation, the overall percentage of stained cells in the cell populations was averaged from four fields [24].…”
Section: Sa B-gal Stainingmentioning
confidence: 99%
“…Telomerase activity was analyzed by a telomeric repeat amplification protocol (TRAP) assay using a telomerase polymerase chain reaction (PCR) enzyme-linked immunosorbent assay kit (Roche, Mannheim, Germany, http://www.roche.com), according to manufacturer's protocol [24]. Briefly, cells (2 3 10 5 ) were harvested for each reaction and centrifuged at 3,000g for 10 minutes at 4°C, washed twice with PBS, incubated for 20 minutes at 4°C with 200 ml lysis buffer, and centrifuged at 16,000g for 20 minutes.…”
Section: Telomerase Activitymentioning
confidence: 99%